Environmental Responsibility, Environmental Concerns, and Green Banking Adoption in Pakistan: Using the Unified Theory of Acceptance and Use of Technology - Abdul Majeed; Abdul Rasheed (Human Behavior and Emerging Technologies)
The banking industry has been criticized for its role in contributing to climate change, whether directly or indirectly. In response to these concerns, the “green banking” concept has emerged as a proactive approach to mitigating banks’ environmental impact. However, there is still limited research on adopting green banking from customers’ perspectives in developing countries, notably Pakistan. Therefore, this research is aimed at exploring and examining the factors influencing customers’ intention to adopt green banking and their usage behavior by employing the unified theory of acceptance and use of technology (UTAUT). The UTAUT model was integrated with customers’ environmental responsibility and environmental concerns to identify the primary drivers of green banking proliferation. The research was carried out in Lahore, Pakistan, and involved 280 customers from private banks, and a convenience sampling technique was employed to gather data. The empirical findings have revealed that facilitating conditions and performance expectancy are the primary drivers of green banking proliferation, followed by environmental responsibility and environmental concerns. The study has discovered that behavioral intention plays a significant mediating role in the relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, environmental responsibility, environmental concerns, and green banking usage behavior. The banking professionals should consider these factors when formulating and advancing green banking products or services and strategies to encourage the widespread adoption of green banking in conventional markets, fostering hope for a more sustainable future. The study provides new insights into customers’ inclination to adopt green banking and their subsequent usage behavior. This research will help to shape future studies in this particular field.